Negotiating Policies and Practices A Systematic Review of Curriculum Enactment in Early Childhood Settings - Novtryananda Maryanti Stefani Ghunu; Anandi Lintang Utari (Bina Nusantara University, 2025)
Early childhood education curriculum implementation is complex and localized, impacted by teachers' attitudes, cultural backgrounds, and professional judgment. This study fills gaps in our knowledge of how early childhood teachers alter, implement, negotiate, and incorporate hidden meanings into curriculum policies in various educational settings. We used a Systematic Literature Review (SLR) to examine 20 Scopus-listed peer-reviewed articles from 2019 to 2025 on early childhood education curriculum implementation. This study found themes synthesis examined teacher adaptation and operational curriculum (17 studies), enactment of official curriculum (18 studies), hidden curriculum (14 studies), and negotiated curriculum and teacher agency (17 studies). The results reveal that it will not be simple to put the curriculum into action. Instead, local requirements, cultural values, and teachers' teaching ideas shape it in a dynamic and intentional manner. Teachers have influence because they adapt content to students' needs, base learning activities on classroom activity, and include moral, ethical, and social elements in hidden curricula. It provides a complete picture of how early childhood and primary school teachers applied the curriculum in practice, adding to research.